Analyzing Students’ Writing Grammatical Problem in the Use of Tenses: The Case of Seventh Grade Student Of Junior High School - Khothibhatul Ummah (ETERNAL (English Teaching Journal), 2018)
Grammar is one of the most difficult capabilities found in English. Grammar difficulty will affect other English skills such as reading, speaking, listening, and writing. Tenses belong to one part of grammar. Most students still struggle to use tenses well. Tenses contained in this grammar material need to be studied so that students can distinguish the time of conversation and the meaning of a sentence and how to make a sentence in accordance with the tenses that have been studied. This research was designed in the form of qualitative research, especially in descriptive method. It meant that the researcher would like to investigate the use of tenses (especially past, present, future, continous, and present perfect) and to identify the grammatical errors in using tense (especially past, present, future, continous,  and present perfect) in students junior high school of seventh grade with close task.